Construction and practice of an innovative general education course of “Medicine + Humanity” under the background of New Medicine - CUI Yan (Jichu yixue yu linchuang, 2022)
With the advance of the construction of “New Medicine”, the establishment of interdisciplinary and innovative courses has become an urgent work and challenge. This paper introduces the goals, methods, contents, practice and feedback of the innovative general education course of “Medicine + Humanity” in Tianjin Medical University. Our study paves the way for the crosstalk and integration of general education courses from different majors.